A NOTE ON THE POPULATION DENSITY OF CLAMS IN THE VELLAR ESTUARY - R, Jayabal; Kalyani, M (Indian Journal of Fisheries, 2011)
The note deals briefly with the observations made in the clam beds in the Vellar estuary with regard to population density, sex ratio, spawning activity and ecological parameters